Movimento morfossintático da língua no autismo. - Vale, Lorena Grace Alves do (2024)
Children with ASD present difficulties in oral and written language and, above all, face challenges in understanding and producing morphosyntactic skills, such as the appropriate morphosyntactic structuring of sentences and the correct use of the language's grammatical rules. These difficulties manifest themselves in different ways, for example: replacing more complex words with simpler ones; omission or misuse of grammatical markers in speech; atypical ordering of words in the linearity of the sentence and difficulty in agreeing between elements in the sentence. In addition to speech symptoms, we believe that our studies can reveal peculiarities in the morphosyntactic functioning of the autistic language. Thus, the thesis has the general objective of investigating movement at the morphosyntactic level of language in children with ASD in its oral modality. The specific objectives are to identify possible morphosyntactic changes in terms of obedience to the language system and evaluate whether these can interfere with semantization, which is the axis of enunciation. The methodology adopted was a qualitative case study type, carried out with six children, who spoke Brazilian Portuguese, who were literate and cared for by the multidisciplinary team at the Association of Parents and Friends of the Exceptional (APAE), in the municipality of Serra Talhada, State of Pernambuco. , in 2022. The enunciative scenes were captured in a naturalistic way by video recordings in psychopedagogical therapy situations and during routine activities in the therapeutic environment. The collected data were analyzed, following the language acquisition enunciative approach of researcher Carmem Luci Silva who, in the light of Émile Benveniste's language theorization, seeks to investigate the constitution of the child as a speaker in their mother tongue, whether oral or graphic, through the relationships that the child maintains with their peers in their linguistic community. The collected records were illustrated in tables with clippings of the enunciative scenes and had their linguistic data transcribed with the help of NVivo software, also reporting speech situations between the child and the therapist. By analyzing the results, we can conclude that the morphosyntactic aspects of the language follow a unique structure in autism, which reveals that between stumbles and successes, there is a unique way of constructing meaning in unexpected ways in enunciation. The inversion of morphosyntactic elements in the phrase's structure seems to be recurrent, which causes a break in syntagmatic linearity and affects the semanticization of the narrative by the speaker. The linguistic manifestations in the materiality of the discourse constituted facts of the language and the subjects, which configured the peculiar functioning of the formal apparatus of enunciation.